Síndrome de Marfan: importância da história familiar - relato de caso - Maria de Fátima Monteiro Pereira Leite; Carolina da Penha Muniz; Carla Verona Barreto Farias; Dulce Helena Gonçalves Orofino; Daltro Castellar Junior; Anneliese Lopes Barth (Sociedade Brasileira de Pediatria, 2023)
We describe a case of Marfan syndrome, referred for evaluation due to an important family history of sudden death. In the first evaluation, he presented dilation of the aortic root in addition to other clinical manifestations of the disease. Our objective is to emphasize the importance of family history as a starting point in Marfan syndrome investigation, in an effort to prevent unfavorable outcomes like aortic dissection and sudden death.